Spectrum of Paediatric Lysosomal Storage Disorders in Oman - Al-Maawali, Almundher A (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2012)
OBJECTIVES: The aim of this study was to look at the spectrum of paediatric lysosomal disorders in Oman. Lysosomal storage disorders (LSDs) are a heterogeneous group of inherited metabolic diseases. Few studies on the birth prevalence and prevalence of LSDs have been reported from the Arabian Peninsula. METHODS: We studied 86 children with LSDs diagnosed over a period of nine years, from June 1998 to May 2007. Detailed clinical data, including age of onset, sex, age and mode of first presentation, and presence of consanguinity were collected. RESULTS: Our data showed the combined birth prevalence for all LSDs in Oman to be around 1 in 4,700 live births. Sphingolipidoses was the most common group of disorder encountered (47.7%), followed by neuronal ceroid lipofuscinoses (NCL) (23.2%) and mucopolysaccharidoses (MPS) (23.2%). The proportion of consanguineous marriages in our series was found to be 87.5%. CONCLUSION: Our data represent the birth prevalence and clinical spectrum of such disorders in Oman, one of the highly consanguineous societies in the Middle East.